The Present and Future of Personalized Nutrition - Nimbe Torres; Armando R. Tovar (Permanyer, 2021)
In recent decades, there has been an increase in the presence of metabolic disorders associated with obesity. Central in the treatment of these conditions, including abnormalities in glucose and lipid metabolism, dietary strategies play an important role. However, dietary recommendations are based on the generalization of nutrient or food intake response for all individuals, which not necessarily impacts the health of all individuals. The concept of personalized nutrition or precision nutrition has been recently developed, which states that diet is not the only factor accountable for metabolic responses such as postprandial glucose peaks, but that other factors are also involved, one of the most important of which is the gut microbiota. Therefore, the future of nutritional interventions is to generate algorithms based on the type of food consumed, biochemical parameters, physical activity, genetic variability, and especially the gut microbiota to predict the type of diet a person requires according to his or her metabolic alterations.